Validating new diagnostic imaging criteria for primary progressive aphasia via anatomical likelihood estimation meta-analyses. - Bisenius, S.; Neumann, J.; Schroeter, M. L. (Eur J Neurol, 2016)
Recently, diagnostic clinical and imaging criteria for primary progressive aphasia (PPA) have been revised by an international consortium (Gorno-Tempini et al. Neurology 2011;76:1006-14). The aim of this study was to validate the specificity of the new imaging criteria and investigate whether different imaging modalities [magnetic resonance imaging (MRI) and fluorodeoxyglucose positron emission tomography (FDG-PET)] require different diagnostic subtype-specific imaging criteria. Anatomical likelihood estimation meta-analyses were conducted for PPA subtypes across a large cohort of 396 patients: firstly, across MRI studies for each of the three PPA subtypes followed by conjunction and subtraction analyses to investigate the specificity, and, secondly, by comparing results across MRI vs. FDG-PET studies in semantic dementia and progressive nonfluent aphasia. Semantic dementia showed atrophy in temporal, fusiform, parahippocampal gyri, hippocampus, and amygdala, progressive nonfluent aphasia in left putamen, insula, middle/superior temporal, precentral, and frontal gyri, logopenic progressive aphasia in middle/superior temporal, supramarginal, and dorsal posterior cingulate gyri. Results of the disease-specific meta-analyses across MRI studies were disjunct. Similarly, atrophic and hypometabolic brain networks were regionally dissociated in both semantic dementia and progressive nonfluent aphasia. In conclusion, meta-analyses support the specificity of new diagnostic imaging criteria for PPA and suggest that they should be specified for each imaging modality separately.
Keywords: Aphasia, Primary Progressive/*diagnostic imaging; Frontotemporal Dementia/*diagnostic imaging/pathology; Humans; *Likelihood Functions; Magnetic Resonance Imaging/*standards; Positron-Emission Tomography/*standards; Practice Guidelines as Topic/*standards; Primary Progressive Nonfluent Aphasia/*diagnostic imaging